Analisis Pelaksanaan Program Pengungkapan Sukarela Terhadap Penerimaan Pajak di Kantor Wilayah Direktorat Jenderal Pajak Jawa Barat I - Tina Septiani; Yeti Apriliawati (Indonesian Accounting Literacy Journal, 2023)
This research was conducted to determine how the Voluntary Disclosure Program was implemented at the Kanwil DJP Jawa Barat I and knowing the effect on tax revenue before, during and after the implementation of the Voluntary Disclosure Program. The purpose of conducting this research was to find out how the Voluntary Disclosure Program (PPS) was implemented within the Kanwil DJP Jawa Barat I, find out taxpayer compliance, and tax revenue within the Kanwil DJP Jawa Barat I after the implementation of the Voluntary Disclosure Program. The research method used is descriptive research with a qualitative approach to answer the first problem formulation and a quantitative approach to answer the second problem formulation The results obtained from this study are the implementation of the Voluntary Disclosure Program followed by 21,339 taxpayers with tax revenues of IDR 3,984,174,278,610. Tax revenue during implementation (January-June 2022) has increased from tax revenue before implementation (July-December 2021) and tax revenue after implementation (July-December 2022) has decreased. This shows that the Voluntary Disclosure Program has an effect on increasing or decreasing tax revenues in the Kanwil DJP Jawa Barat I. Keywords: Tax, Voluntary Disclosure Program, Tax Revenue